Microstructure and Mechanical Behavior of Al-Mg Composites Synthesized by Reactive Sintering - Rub Nawaz Shahid; Sergio Scudino (Metals, 2018)
Lightweight metal matrix composites are synthesized from elemental powder mixtures of aluminum and magnesium using pressure-assisted reactive sintering. The effect of the reaction between aluminum and magnesium on the microstructure and mechanical properties of the composites due to the formation of β-Al3Mg2 and γ-Al12Mg17 intermetallics is investigated. The formation of the intermetallic compounds progressively consumes aluminum and magnesium and induces strengthening of the composites: the yield and compressive strengths increase with the increase of the content of intermetallic reinforcement at the expense of the plastic deformation. The yield strength of the composites follows the iso-stress model when the data are plotted as a function of the intermetallic content.